The Economic History of the American Economic Review: A Century's Explosion of Economics Research - Margo, Robert A (American Economic Review, 2011)
Written in celebration of the 100th anniversary of the American Economic Review, this paper recounts the history of the journal. The recounting has an analytic core that sees the American Economic Association as an organization supplying goods and services to its members, one of which is the Review. Early in its history the Review was a multipurpose publication with highly disparate content. Over time the economics profession expanded and more economics research was produced, primarily in the form of journal articles. Editors accommodated this shift by allocating more resources to the refereeing and editing process and more space to research papers. (JEL A14, B19, B29)